Chromosome 15q13.1q13.2 microdeletion in a foetus with severe congenital heart defects: A case report - Thi Ha Vu; Thi Hai Hoang; Thi Sim Nguyen; Khanh Dung Ho; Thi Kim Phuong Doan (Vietnam Journal of Science, Technology and Engineering)
Congenital heart disease (CHD) is a complex condition affecting the heart’s structure and function, leading to serious health problems. While the cause of CHD is not well understood, researchers have identified copy number variations (CNVs) as potential contributors to its pathogenesis. One such CNV is the rare chromosome 15q13 microdeletion, but its role in CHD remains unclear. In a 22-week gestation foetus, severe congenital heart defects were detected by colour Doppler ultrasound imaging. Array comparative genomic hybridisation (aCGH) was performed, revealing a 1.1 Mb deletion of the chromosome 15q13.1-q13.2 region containing five genes (APBA2, NSMCE3, TJP1, FAM189A1, LOC100130111). However, further chromosomal G-banding revealed no abnormal karyotype. Parental aCGH testing determined that this mutation was de novo. This report demonstrates the potential association between chromosome 15q13.1-q13.2 microdeletion and foetal congenital heart defects for the first time. The use of aCGH in foetuses with abnormal cardiac development diagnosed by routine cardiac colour Doppler ultrasound imaging is recommended for the early detection of congenital genetic abnormalities. This information can provide valuable insight for prenatal diagnostic consultation and decisions regarding pregnancy termination.